Navigating autism representation in 'extraordinary attorney woo': A Korean drama perspective - Majid Wajdi; Selvie Ratna Ivone Mandang; Budi Susanto; Abdurrahim Abdurrahim; Ratna Dewi (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This review examines the Korean drama Extraordinary Attorney Woo, which narrates the life of Woo Young-Woo, a lawyer with Autism Spectrum Disorder (ASD). The series portrays the unique challenges and abilities of individuals with ASD, combining social difficulties and limited empathy with exceptional memory and intelligence. The drama seeks to inspire audiences by illustrating Woo's journey towards independence while confronting societal stigma and prejudice. The objective of this review is to critically analyse the portrayal of ASD in the series, highlighting its role in shaping public perception and fostering greater understanding and empathy for individuals with autism. The data collection involved document analysis, including a detailed review of the drama’s episodes and a literature review on autism representation in media. This method enabled a comparison of the series' portrayal with existing studies and established characteristics of ASD. The analysis focused on the authenticity and sensitivity of the depiction, its adherence to or deviation from ASD traits, and its impact on public perceptions. The findings reveal that Extraordinary Attorney Woo successfully challenges stereotypes, promotes awareness, and provides an authentic representation of ASD. The drama emphasizes neurodiversity while showcasing the challenges and triumphs of individuals with autism. However, some dramatizations of ASD traits for narrative purposes were noted, highlighting the need for careful balance in future portrayals. In conclusion, Extraordinary Attorney Woo is a significant step towards fostering inclusivity and understanding. Recommendations include further collaboration with experts to ensure accuracy and continued focus on breaking stereotypes in media representations of autism.